The H 4 model revisited within the framework of the G-particle-hole Hypervirial equation - Valdemoro, Carmela (2012)
In this paper we report the results obtained when calculating the electronic structure of the H 4 molecular system within the framework of the G-particle-hole Hypervirial equation (GHV). This method determines directly the G-particle-hole matrix of the state considered without a previous knowledge of the wave-function. Our primary aim is to compare the GHV performance with that of other standard ab initio methods having as ultimate reference the FCI results, when the system considered is strongly correlated. © 2011 Elsevier B.V. All rights reserved.